BUDAYA MEMBUKUKKAN BADAN (OJIGI) DAN FUNGSINYA DALAM KEHIDUPAN MASYARAKAT JEPANG - Budi Mulyadi (KIRYOKU, 2017)
This title resserach is Ojigi Culture (Bow the body) and Its Function in Japanese life.  Ojigi is a Japanese identity. Ojigi as a culture that is done massively respect and infiltrate in Japanese people. Bow the body activity is not only routine and glance physical This activity has deep meaning, goal, or lesson and value. The purpose of this resseach are, first: achieving the right ilustration about Ojigi, the second: obtaining image about Ojigi meaning and the function of ojigi. This ressearch is ressearch model that combine between literary review and field ressearch model.   Material object of this ressearch is Ojigi. The formal object of this ressearch is analyzing  Ojigi culture deeply to find hidden philosophy or values includes inside. The main method used in this ressearch are interpretation and analyzing.